Analysis of the Current Status of Self-Management Behaviors and Factors Affecting Self-Management in Elderly Empty Nesters with Comorbid Hypertension and Type 2 Diabetes Mellitus, a Cross-Sectional Study From the Community - Li F; Cao Y; Xie X; Li M; Cheng T (Risk Management and Healthcare Policy, 2025)
Fang Li,1,* Yuzhong Cao,1,* Xuejuan Xie,2 Mengwei Li,1 Tengteng Cheng1 1College of Nursing, Gansu University of Chinese Medicine, Lanzhou, Gansu, People’s Republic of China; 2College of Nursing, Jiamusi Vocational College, Jiamusi, Heilongjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang Li, College of Nursing, Gansu University of Chinese Medicine, 35 Dingxi Road East, Lanzhou, Gansu, 730000, People’s Republic of China, Email 2862422633@qq.comPurpose: This study aimed to investigate disease self-management and its influencing factors among empty nesters with comorbid hypertension and type 2 diabetes mellitus in the Chinese community.Patients and Methods: A questionnaire was administered to 385 empty nesters in the community with comorbid hypertension and type 2 diabetes mellitus, including general information about the patients, the conditions of hypertension and type 2 diabetes mellitus, and self-management scores. The results were analysed using independent samples t-test, one-way ANOVA and multiple linear regression.Results: Disease self-management ability among 360 empty nesters in the community with comorbid hypertension and type 2 diabetes mellitus was low to moderate level. The results of the multiple linear regression analysis showed that age, education, healthcare payment method, and systolic blood pressure were common influences on self-management of the two diseases; hypertension classification, body mass index, and 2-hour postprandial blood glucose were influences on self-management of hypertension; and diabetes treatment method and residence mode were influences on self-management of type 2 diabetes mellitus.Conclusion: Primary healthcare providers need to pay close attention to the self-management skills of empty nesters with comorbid hypertension and type 2 diabetes mellitus in the community, especially in terms of disease monitoring and dietary management. Effective self-management health education, including sustained and effective lifestyle interventions, should be provided as early as possible for those living alone, newly diagnosed, less educated, and with limited healthcare resources, and the addition of elements of Chinese medicine health management, can also be considered to play a role in integrating prevention and treatment.Keywords: comorbid, type 2 diabetes mellitus, hypertension, self-management, empty-nest, elderly